2014
DOI: 10.12938/bmfh.33.25
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Lactic Acid Bacteria in a Commercial Probiotic Culture

Abstract: The aim of the present study was to describe the identification and characterization (physiological properties) of two strains of lactic acid bacteria (LAB 18 and 48) present in a commercial probiotic culture, FloraMax®-B11. Isolates were characterized morphologically, and identified biochemically. In addition, the MIDI System ID, the Biolog ID System, and 16S rRNA sequence analyses for identification of LAB 18 and LAB 48 strains were used to compare the identification results. Tolerance and resistance to acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 30 publications
1
58
1
Order By: Relevance
“…Menconi et al (2014), evaluating two samples of lactic acid bacteria present in a commercial probiotic and incubated for two and four hours, respectively, at temperatures of 15ºC and 45ºC, detected growth under microaerophilic conditions. In the present study, the bacteria in the commercial probiotic product maintained at 25ºC grew under both aerobiosis and anaerobiosis up to six hours of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Menconi et al (2014), evaluating two samples of lactic acid bacteria present in a commercial probiotic and incubated for two and four hours, respectively, at temperatures of 15ºC and 45ºC, detected growth under microaerophilic conditions. In the present study, the bacteria in the commercial probiotic product maintained at 25ºC grew under both aerobiosis and anaerobiosis up to six hours of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…All the isolated strains were able to tolerate pH (02-08) and presence of bile salt (0.5-2.0%) even for 24 hours of incubation at 37 o C. NaCl is an inhibitory substance which inhibit growth of many types of bacteria, therefore high salt tolerance is considered as a criteria of probiotic property. So, it was essential to test the NaCl tolerance of the isolates (Menconi et al, 2014). Hoque et al (2010) observed the NaCl (1-9%) tolerance of their Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that these two phenomena are related: the food sources and 482 molecular cues that microbes encounter in their environment affect their expression of proteins and 483 compounds (or community-level behavior such as aggregation and biofilm formation) that convey the 484 probiotic's beneficial effect. Further experiments are needed to measure a correlation between the 485 metabolic profiles and probiotic properties of these particular strains, similar to a study of two lactic acid 486 bacteria from the commercial culture FloraMax®-B11 [54]. Several examples of the relationship 487 between nutrient sources and bacterial probiotic phenotype include: increased resistance of L. plantarum 488 to gastric juices when growth with pectin or inulin compared to glucose [47]; differences in cell surface 489 hydrophobicity, cell surface protein and exopolysaccharide production of L. rhamnosus grown on 490 fructose, mannose, or rhamnose [55]; and increased the adhesion of Lactobacillus acidophilus to mucin 491 or intestinal cells in the presence of fructooligosaccharides (FOS), cellobiose, or polydextrose [56].…”
Section: Evaluation Of Product Labels and Quantification Of Publishedmentioning
confidence: 99%